The math adventurers share a camping trip - Chapman, Sital Gorasia (Chapman, Sital Gorasia. Math adventurers., 2024)
"Beep and Boots are going on a camping trip in the great outdoors. They've got a warm sleeping bag each, a nice cozy tent each, and strawberries to share. But they realize there are not enough tent pegs! Can they learn to divide up what they have and put up their tents before it's time for bed?"--Provided by publisher.